2015
DOI: 10.2337/dc15-0466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Energy Diets Differing in Fiber, Red Meat, and Coffee Intake on Cardiac Autonomic Function in Obese Individuals With Type 2 Diabetes

Abstract: OBJECTIVEThe autonomic nervous system (ANS) regulates both the cardiovascular system and energy balance and is disturbed in diabetes and obesity. The effect of different approaches of caloric restriction on ANS function has not been assessed in individuals with diabetes. Thus, we sought to determine whether low-energy diets differing in fiber, red meat, and coffee intake exert differential effects on cardiac autonomic function. RESEARCH DESIGN AND METHODSIn this randomized parallel-group pilot trial, obese pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 39 publications
3
44
0
1
Order By: Relevance
“…According to the 2015 Dietary Guidelines for Americans, eating patterns that include lower intake of red meats are associated with reduced risk of obesity . However, findings from randomized controlled trials largely find no detrimental impact of lean red meat consumption on markers of cardiometabolic health during weight loss and weight maintenance . Red meat is a major contributor to overall protein intake and represents 58% of all meat consumption in the United States .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the 2015 Dietary Guidelines for Americans, eating patterns that include lower intake of red meats are associated with reduced risk of obesity . However, findings from randomized controlled trials largely find no detrimental impact of lean red meat consumption on markers of cardiometabolic health during weight loss and weight maintenance . Red meat is a major contributor to overall protein intake and represents 58% of all meat consumption in the United States .…”
Section: Introductionmentioning
confidence: 99%
“…Previous randomized clinical studies demonstrated that lean beef and pork can be effectively incorporated into dietary patterns for improving cardiometabolic health during weight maintenance conditions. At least two randomized clinical trials found that including red meat in energy‐restricted diets does not negatively influence weight loss or improvements in cardiometabolic health . However, previous weight loss intervention trials were limited by relatively small sample sizes, absence of a HP control diet with no red meat and the manipulation of multiple dietary components .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANS dysfunction and increased sympathetic activity have been directly correlated with obesity (Piestrzeniewicz et al, 2008; Straznicky et al, 2009; Lambert E. et al, 2010; Lambert G. W. et al, 2010). Moreover, weight reduction significantly improves HRV and reduces ANS imbalances (Karason et al, 1999; Maser et al, 2007; Nault et al, 2007; Perugini et al, 2010; Ravussin, 2010; Casellini et al, 2015, 2016; Ziegler et al, 2015a). To evaluate the ability to reverse autonomic imbalance, we examined sudomotor function and HRV measurements in obese patients undergoing bariatric surgery.…”
Section: Prevention and Reversibility Of Cardiac Autonomic Neuropathymentioning
confidence: 99%
“…Zastosowanie diety ubogokalorycznej u otyłych pacjentów z T2DM przez 8 tygodni wiąże się z poprawą parasympatycznej regulacji rytmu serca niezależnie od konsumpcji czerwonego mięsa czy zawartości błonnika [30]. Z drugiej strony jednak nie można wykluczyć, że poszczególne składniki diety nie wywierają wpływu na układ autonomiczny a obserwowany efekt wynika jedynie ze zmniejszenia masy ciała pacjentów [31][32].…”
Section: Dietaunclassified